State, Islam, and Gender : Dynamics of Marital Rape Law in Indonesia - Pitrotussaadah Pitrotussaadah; Eva Fadhilah (Al-Qadha : Jurnal Hukum Islam dan Perundang-Undangan, 2023)
Marital rape, which is an act of sexual violence in marriage, is often debated among the public because it is considered an act that is impossible to happen. There is debate about responding to acts of marital rape among the community, which is the background for writing this article in a review of positive law, Islamic law, and gender justice. The purpose of this research is to understand and analyze the dynamics of rape marital law in Indonesia according to positive law, Islamic law, and gender. Using a qualitative method with a normative legal approach, this paper describes and analyzes the laws, books, and articles related to this research. The results found from this study are that marital rape is included in the crime of sexual violence, although it is not explained in detail regarding the criminal sanctions for the perpetrators. This shows that Indonesia's positive law has not touched on marital rape in detail. Marital rape is not justified in Islamic law; this can be seen from the verses of the Quran, which emphasize a good relationship between husband and wife. Based on gender justice, it is the wife who becomes the victim of marital rape because the husband thinks that he is at a higher level, so the wife must obey her husband's orders because it is an obligation, while the husband ignores the wife's rights.